2016
DOI: 10.1002/jmv.24748
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high‐risk human papillomavirus infection among women in Shaanxi province of China: A hospital‐based investigation

Abstract: This study aimed to investigate the characteristics of female high-risk human papillomavirus (HR-HPV) infection in Shaanxi province of China. A total of 14 111 women were enrolled for HPV genotyping test, and a cytology, and/or cervix biopsy were performed in partial women. Of these women, the HPV infection rate was 30.21%, and 26.73% were caused by HR-HPV. The most common HR-HPV genotypes were HPV-16, HPV-58, HPV-52, HPV-18, and HPV-31. The prevalence of HR-HPV among women older than 50 years was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
4
7
0
Order By: Relevance
“…24 In mainland China, various authors have noted significant geographical variation. Li et al reported Sichuan at 19.9%, 25 Shanxi was 26.7% reported by Cao et al,26 and Guangdong was 7.3% reported byZhao et al 27 In our study, the overall prevalence of cervical HPV infection is 9.1% (range 6.3% to 12.9% by region). This was lower than the 19.0% prevalence noted byLi et al in their systematic review of the epidemiology of hr-HPV infections conducted in mainland China 28.…”
supporting
confidence: 46%
“…24 In mainland China, various authors have noted significant geographical variation. Li et al reported Sichuan at 19.9%, 25 Shanxi was 26.7% reported by Cao et al,26 and Guangdong was 7.3% reported byZhao et al 27 In our study, the overall prevalence of cervical HPV infection is 9.1% (range 6.3% to 12.9% by region). This was lower than the 19.0% prevalence noted byLi et al in their systematic review of the epidemiology of hr-HPV infections conducted in mainland China 28.…”
supporting
confidence: 46%
“…HPV genotypes were determined according to the HPV genotypes schematic diagram: blue and purple dots were considered as HPV positive. Twenty-one HPV genotypes included 15 high-risk genotypes (16,18,31,33,35,39,45, 51, 52, 53, 56, 58, 59, 66 and 68) and 6 low-risk genotypes (6,11,42,43,44 and CP8304). Participants with any of HPVpositive genotypes were regarded as HPV-infected (whether or not coinfected by other HPV genotypes).…”
Section: Hpv Detectionmentioning
confidence: 99%
“…[4][5][6][7][8] Development of cervical cancer is a long-term process with multiple stages. Although a persistent human papillomavirus (HPV) infection, especially high-risk human papillomavirus (HR-HPV) infection, is necessarily a causal factor in cervical carcinogenesis, [9][10][11] not all women infected with HPV develop cervical cancer, indicating that other factors are involved in cervical carcinogenesis along with HPV. 12,13 In recent years, an increase in industrial production has resulted in increased environmental pollution, which has become more and more serious.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of the same HPV type are referred to variant lineages and sublineages based on the complete genome nucleotide sequences differing approximately 1%-10% and 0.5%-1%, respectively [6]. HPV16, 18, 52 and 58 have been found to be the top four prevalent high-risk HPVs among Chinese females [7][8][9][10]. So far, multiple variant lineages and sublineages have been designated to HPV16 (A1-A4, B1-B4, C1-C4, D1-D4) [6,11,12], HPV18 (A1-A5, B1-B3, C) [6], HPV52 (A1-A2, B1-B2, C1-C2, D) [6] and HPV58 (A1-A3, B1-B2, C, D1-D2) [6].…”
Section: Introductionmentioning
confidence: 99%